On Λ-Fibonacci difference sequence spaces of fractional order - Taja Yaying (Dera Natung Government College Research Journal)
In this article, we introduce -Fibonacci difference operator of fractional order  which is obtained by the composition of -Fibonacci matrix  and backward fractional difference operator  defined by  and introduce the sequence spaces  and  We give some topological properties, and obtain the Schauder basis of the new spaces.